Analyse This: The Eight-Box Method of Case Analysis - Sankaran, Rajan (Homœopathic Links, 2018)
The main problem which students face is to synthesise the data received in case-taking and arrive at a remedy. Classifying the data of the chief complaint, the physical and mental generals, and the particulars into eight boxes has been developed as a tool in establishing the simillimum. This tool also proves extremely useful in the evaluation of symptoms when a case is re-taken and also in evaluating the progress of the patient during a follow-up.
Keywords: Case-taking; case analysis; synergy approach; Eight-Box Method; Capsicum annuum